Nickel-Catalyzed Decarbonylative Alkynylation of Acyl Fluorides with Terminal Alkynes under Copper-Free Conditions - Chen, Qiang; Fu, Liyan; You, Jingwen; Nishihara, Yasushi (Synlett, 2020)
Nickel-catalyzed decarbonylative alkynylation of acyl fluorides with terminal silylethynes under copper-free conditions is described. This newly developed method has a wide substrate scope, affording internal silylethynes in moderate to high yields. The formation of 1,3-diynes as homocoupled products and conjugate enones as carbonyl-retentive products were effectively suppressed.
Keywords: nickel catalysis; decarbonylation; silylalkynes; alkynylation; acyl fluorides; sila-Sonogashira–Hagihara reaction